Ex situ synthesis and optical properties of ZnO-PbS nanocomposites - Ntwaeaborwa, O. M.; Kroon, R. E.; Kumar, V.; Dubroca, T.; Ahn, J. -P.; Park, J. -K.; Swart, H. C. (PERGAMON-ELSEVIER SCIENCE LTD, 2009)
Zinc oxide (ZnO) and lead sulphide (PbS) nanoparticles separately synthesized by a precipitation method were combined by an ex situ route to prepare ZnO-PbS nanocomposites with different molar ratios of ZnO and PbS. The structure and morphology of the ZnO, PbS and ZnO-PbS samples were analyzed with X-ray diffraction (XRD) and high-resolution transmission electron microscopy (HRTEM). A UV-vis spectrophotometer was used to collect the absorption and 325 nm He-Cd and 488 nm Ar lasers were used to collect the photoluminescence data from the samples. ZnO nanoparticles showed a broad and stable emission peak at similar to 570 nm, while a strongly quantum confined emission from PbS nanoparticles was detected at similar to 1344-1486 nm. The ZnO-PbS nanocomposites exhibited dual emission in the visible and near-infrared (NIR) regions that is associated with defects and recombination of excitonic centres in the ZnO and PbS nanoparticles, respectively. The PL intensity of the visible emission from the ZnO-PbS nanocomposite was shown to increase when the ZnO to PbS molar ratio was 5:1 and the emission was almost quenched at molar ratios of 1:1 and 1:5. For different molar ratios of ZnO to PbS, the PL intensity of the NIR emission from the ZnO-PbS nanocomposites was more intense than that of PbS nanoparticles. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: QUANTUM DOTS; NANOPARTICLES; PHOTOLUMINESCENCE; TEMPERATURE; GROWTH